Hybrid Precoding Aided Fast Frequency-Hopping for Millimeter-Wave Communication - Abbas Ahmed (IEEE, 2021)
The deployment of the Millimeter-Wave (mm-Wave) band in 5G and beyond wireless communications networks is one of the emerging fields owing to its potential of providing extensive bandwidth. Frequency Hopping (FH) has a high potential for use in wireless networks due to its key advantages of spreading the interference over wide bandwidth and of providing diversity gain in counteracting frequency-selective fading. Furthermore, Fast Frequency Hopping (FFH) intrinsically amalgamated with directional Beamforming (BF) may overcome the impairments because of the path-loss of mm-Wave communications. Thus, we propose FFH assisted base-band precoding aided BF for mitigating the mm-wave channel impairments imposed by both fading as well as path loss, whilst relying on a minimal range of radio frequency chains. The mathematical analysis and simulation results demonstrate that hybrid precoded FFH is indeed a promising high-capacity technique of attaining both time- and frequency-domain diversity gains for the mm-Wave communications.